G-SOMO - Douzas, Georgios (2021)
Douzas, G., Rauch, R., & Bacao, F. (2021). G-SOMO: An oversampling approach based on self-organized maps and geometric SMOTE. Expert Systems with Applications, 183, 1-11. [115230]. https://doi.org/10.1016/j.eswa.2021.115230---%ABS1%